A Scalable Methylamine Gas Healing Strategy for High‐Efficiency Inorganic Perovskite Solar Cells. Issue 17 (19th March 2019) - Shao, Zhipeng; Wang, Zaiwei; Li, Zhipeng; Fan, Yingping; Meng, Hongguang; Liu, Ranran; Wang, Yan; Hagfeldt, Anders; Cui, Guanglei; Pang, Shuping
Abstract: An easy and scalable methylamine (MA) gas healing method was realized for inorganic cesium‐based perovskite (CsPbX3 ) layers by incorporating a certain amount of MAX (X=I or Br) initiators into the raw film. It was found that the excess MAX accelerated the absorption of the MA gas into the CsPbX3 film and quickly turned it into a liquid intermediate phase. Through the healing process, a highly uniform and highly crystalline CsPbX3 film with enhanced photovoltaic performance was obtained. Moreover, the chemical interactions between a series of halides and MA gas molecules were studied, and the results could offer guidance in further optimizations of the healing strategy. Abstract : A facile and scalable methylamine (MA) gas healing method for inorganic cesium‐based perovskite (CsPbX3 ) layers is based on incorporating a certain amount of MAX (X=I or Br) initiators into the raw film. The excess MAX accelerated the absorption of the MA gas into the CsPbX3 film and the formation of a liquid intermediate phase, enabling the formation of a highly uniform and crystalline CsPbX3 film with enhanced photovoltaic performance.